2016
DOI: 10.20453/rnp.v79i3.2922
|View full text |Cite
|
Sign up to set email alerts
|

Revisión sobre el uso del mate de hoja de coca en la prevención del mal agudo de montaña.

Abstract: Revisión sobre el uso del mate de hoja de coca en la prevención del mal agudo de montaña.Review on the use of coca tea in prevention of acute mountain sickness.Joel Salinas-Piélago 1,a RESUMEN El número de turistas que viajan a zonas de gran altitud en países andinos se está incrementando en los últimos años, con aumento concomitante del riesgo de desarrollar el mal agudo de montaña. En las zonas alto andinas el mate de hoja de coca es usado frecuentemente para la prevención de este problema, pero las evidenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Although acetazolamide is the most commonly used preventive medication, [25][26][27][28] only a small fraction (5%) of the medical students identified acetazolamide as such, and only 2 respondents reported using it properly. A previous study reported that only 9% of tourists knew about acetazolamide as a preventive measure.…”
Section: Discussionmentioning
confidence: 99%
“…Although acetazolamide is the most commonly used preventive medication, [25][26][27][28] only a small fraction (5%) of the medical students identified acetazolamide as such, and only 2 respondents reported using it properly. A previous study reported that only 9% of tourists knew about acetazolamide as a preventive measure.…”
Section: Discussionmentioning
confidence: 99%
“…It is, of course, easy to criticise the shortcomings of research on coca and its physiological effect on humans in earlier times considering the changing worldviews, personal motivations, differing perceptions, and often crude research methods with basic equipment. Relating to the use of coca to prevent AMS in travellers, the lack of efficacy studies has been noted [6, 19, 20, 143]. However, to then conclude that coca ‘does not work’ is premature since we do not know, precisely because there are no such studies.…”
Section: Introductionmentioning
confidence: 99%